Critical theory and the ontology of "religion": A response to Thomas Lynch - Schilbrack, Kevin (Critical research on religion, 2017)
Thomas Lynch has proposed that scholars of religion can profitably follow Sally Haslanger's lead and treat "religion," as she treats race, as a social construction. He argues that this proposal resembles my treatment of "religion" in Philosophy and the Study of Religions, but it goes further by treating "religion" as what Haslanger calls a strongly pragmatic social construction, that is, a category that is solely the product of the use of the concept and which does not capture any feature in the world. In this response, I clarify that this argument can be made in a way that is stronger and closer to that of Haslanger if one adopts the position she calls "promiscuous realism."